(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: Objective: Describe the current status of overweight and obesity and some related factors of 515 students of Nguyen Thi Minh Khai High School, Hanoi City in 2024. Research subjects and methods: Cross-sectional descriptive study conducted in November-December 2024. Subject and method: A cross-sectional descriptive study was conducted in November to December 2024. Results: Of the 515 students participating in the study, 286 were female (55.53%). The rate of overweight students increased gradually by grade, from 13.37% in grade 10 to 13.71% in grade 11, with the highest rate being 19.05% in grade 12. The study results also showed that the rate of overweight and obesity among male students was 20.52% and 3.49%, while the rate of obesity among female students was only 11.19% and 1.75%, respectively. Students who regularly ate cakes late at night had a 1.84 times higher risk of TC/BP than those who did not (p = 0.015; 95% CI: 1.13 – 2.98). Students who consumed potato chips, snacks, and junk food in the evening had a 1.91 times higher risk of TC/BP than those who did not consume them (p = 0.010; 95% CI: 1.17 – 3.11). Male gender was the strongest factor associated with overweight/obesity (OR=3.22; p=0.001). Skipping breakfast also significantly increased the risk (OR=2.62; p=0.024). Frequent fast food consumption was significantly associated with overweight/obesity (OR=2.07; p=0.038). Conclusion: High-school students participating in the study had a relatively high rate of TCBP and a statistically significant association with a number of poor nutritional habits.